2011
DOI: 10.1182/blood-2010-04-281394
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer–cell differentiation by myeloid progenitors

Abstract: IntroductionHematopoietic stem cells (HSCs) give rise to all blood lineages. 1 As HSCs differentiate along one lineage, they gradually lose the ability to develop into other lineages. 2 Hematopoietic differentiation involves lineage commitment, defined here as the initiation of developmental program(s) that lead to a particular cell fate. The accompanying inability to differentiate into other lineages has been referred to as lineage maintenance. 3 Lineage commitment and lineage maintenance are complementary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 55 publications
4
105
1
3
Order By: Relevance
“…NK/T precursors will afterwards give rise to NK precursors (NKPs), and lastly immature NK (iNK) and mature NK cells. Nevertheless, there is currently a debate regarding other NK cell precursors; a recent study by Grzywacz et al 56 provided new insights into Abbreviations: ALL, acute lymphoblastic leukemia; AML, acute myeloid leukemia; CML, chronic myeloid leukemia; MRCC, metastatic renal cell carcinoma; NK, natural killer.…”
Section: Nk Cell Developmentmentioning
confidence: 99%
“…NK/T precursors will afterwards give rise to NK precursors (NKPs), and lastly immature NK (iNK) and mature NK cells. Nevertheless, there is currently a debate regarding other NK cell precursors; a recent study by Grzywacz et al 56 provided new insights into Abbreviations: ALL, acute lymphoblastic leukemia; AML, acute myeloid leukemia; CML, chronic myeloid leukemia; MRCC, metastatic renal cell carcinoma; NK, natural killer.…”
Section: Nk Cell Developmentmentioning
confidence: 99%
“…others, the contribution of lymphoid [29] and myeloid [30] pathways to NK cell development from CD34 + stem cells is still a controversial issue. Additionally, it would be of interest to further characterize and directly compare ex vivo generated NK to the subsets of NK cells in PB to achieve a better understanding of the immunological and therapeutic properties of the generated cells.…”
Section: Lehmann Et Almentioning
confidence: 99%
“…In vitro models of NK-cell differentiation from CD34 + cell precursors may give rise to a heterogeneous ILC repertoire, and provide a useful tool to characterize factors that might modulate such process [28,[41][42][43]. In this context, we previously showed that IL-8 favors NK-cell differentiation, while IL-1β-releasing AML blasts may modulate CD161 + CD56 + cell differentiation, suggesting that inflammatory cytokines may influence such process [27,38].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β exerts its effects at early stages of differentiation, as revealed by the expression of LFA-1 and by the increase in ID2 and E4BP4 mRNA relative expression observed in CD34 + -derived precursors after only 4 days of culture. Finally, we show that IL-1β may exert a direct effect on LFA-1 − ILC3-like cells present in the cultures, inducing the acquisition of NK-cell markers, EOMES TF, cytolytic granules, and IFN-γ expression, paralleled by a decrease of RORγt TF.In vitro models of NK-cell differentiation from CD34 + cell precursors may give rise to a heterogeneous ILC repertoire, and provide a useful tool to characterize factors that might modulate such process [28,[41][42][43]. In this context, we previously showed that IL-8 favors NK-cell differentiation, while IL-1β-releasing AML blasts may modulate CD161 + CD56 + cell differentiation, suggesting that inflammatory cytokines may influence such process [27,38].…”
mentioning
confidence: 99%